2016
DOI: 10.1080/11250003.2016.1268655
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of the Italian roe deer (Capreolus capreolus italicus) (Mammalia: Cervidae) from two protected areas

Abstract: The Italian roe deer is classified as "vulnerable" in the International Union for Conservation of Nature Red List of Threatened Species, as the few specimens of this endemism may have a high risk of extinction. Conservation efforts for the Italian roe deer cannot prescind from the study of the feeding habits of the taxon. Therefore, in the present study, the spring diet composition of the Italian roe deer from two protected areas was estimated by using the micro-histological technique of faecal analysis. Univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…The remarkable presence of roe deer in the plots can explain the reduced number of herbaceous species with a relevant utilisation in our trial, as this animal has a selective behaviour, and this confirms the findings of Freschi et al (2017) who reported that a great amount of roe deer diet was composed by a reduced number of preferred vegetal species.…”
Section: Articlesupporting
confidence: 79%
See 1 more Smart Citation
“…The remarkable presence of roe deer in the plots can explain the reduced number of herbaceous species with a relevant utilisation in our trial, as this animal has a selective behaviour, and this confirms the findings of Freschi et al (2017) who reported that a great amount of roe deer diet was composed by a reduced number of preferred vegetal species.…”
Section: Articlesupporting
confidence: 79%
“…Results are in line with previous researches performed utilising the same methodology in mountain environment (Cervasio et al, 2009) that report high changes in wild animal intake on grassland among different periods. In this way wildlife can show an opportunistic behaviour in relation to forage availability (Freschi et al, 2017).…”
Section: Speciesmentioning
confidence: 99%
“…Roe deer is a highly selective feeder [65–66] that can also exhibit opportunistic behavior in relation to food resource availability in a given place, season and/or year [67]. Forest productivity—used here as a proxy of food availability [41] during the last part of gestation, the birth period, and the lactation—sped up mandible growth.…”
Section: Discussionmentioning
confidence: 99%
“…In cold months, porcupines mainly feed on underground vegetal organs (bulbs, tubers and roots), whereas a preference for stems, fruits and epigeal plant parts is shown during spring and summer [21,33,34]. Therefore, in warm months, porcupines may compete for food with native ungulates feeding in open areas, e.g., the roe deer, also in Italy [35][36][37]. The defense strategies by the crested porcupine toward potential predators and competitors include four displays, characterized by increasing aggressiveness [38,39]: (i) dorsal quill and crest erection (which is sufficient for over 50% of interactions); (ii) tail rattling through rattle quills; (iii) hind-foot stamping and growling; and (iv) backyard/sideways attack.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work was to describe interspecific interactions occurring between roe deer and crested porcupines at feeding sites (i.e., fallows and ecotones). We expected that most direct interactions would occur in warm months (spring and summer), i.e., when diet overlap amongst these species is likely to be the highest [33,37].…”
Section: Introductionmentioning
confidence: 99%